A Schulman expands in China with new colour masterbatch facility. Issue 7 (July 2016) - Unknown
Abstract : International compound and masterbatch supplier A. Schulman, Inc has expanded its production capacity in China with the official opening of a new colour masterbatch facility in Changshu, in the country's Jiangsu Province north of Shanghai. Output from its second wholly-owned plant in China will serve growing demand in the region, the company says. It already has a facility in Dongguan, Guangdong Province, where it has recently been investing in additional capacity for masterbatch and engineering plastics production [ ADPO, February 2015].